2019
DOI: 10.1038/s41419-019-2132-x
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2-associated athanogene 5 (BAG5) regulates Parkin-dependent mitophagy and cell death

Abstract: As pathogenic Parkin mutations result in the defective clearance of damaged mitochondria, Parkin-dependent mitophagy is thought to be protective against the dopaminergic neurodegeneration observed in Parkinson’s disease. Recent studies, however, have demonstrated that Parkin can promote cell death in the context of severe mitochondrial damage by degrading the pro-survival Bcl-2 family member, Mcl-1. Therefore, Parkin may act as a ‘switch’ that can shift the balance between protective or pro-death pathways depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…Much like PINK1, Parkin has been described as a neuroprotective agent (Feany and Pallanck 2003). Several interactions with apoptotic proteins have been described, including BCL-x L and BAG5 (De Snoo et al 2019;Hollville et al 2014). Parkin has also been suggested to directly influence apoptosis by ubiquitinating the BH3-binding site of BAK (Bernardini et al 2019).…”
Section: Parkin Activation Can Both Prevent and Promote Cell Deathmentioning
confidence: 99%
“…Much like PINK1, Parkin has been described as a neuroprotective agent (Feany and Pallanck 2003). Several interactions with apoptotic proteins have been described, including BCL-x L and BAG5 (De Snoo et al 2019;Hollville et al 2014). Parkin has also been suggested to directly influence apoptosis by ubiquitinating the BH3-binding site of BAK (Bernardini et al 2019).…”
Section: Parkin Activation Can Both Prevent and Promote Cell Deathmentioning
confidence: 99%
“…Interestingly, unlike the interaction between BAG5 and p62, the association of BAG5 with this complex was at least partially facilitated by Hsp70 ( Beilina et al, 2014 ). More recently, we have demonstrated that BAG5 also modulates parkin-dependent mitophagy suggesting that this co-chaperone may have a more general role in regulating these processes ( De Snoo et al, 2019 ). Further investigation will be required to understand the mechanisms by which this occurs and the role that other BAG proteins may play in these complex intracellular processes required to maintain proteostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that BAG5 functionally interacts with LRRK2 to promote turnover of the TGN ( Beilina et al, 2014 ) and inhibits parkin-mediated mitophagy ( De Snoo et al, 2019 ), it may also be possible that BAG5 has a downstream inhibitory effect on autophagic flux, which, in turn, slows the degradation of p62 and alpha-synuclein via the ALP and promotes the accumulation of p62 and alpha-synuclein aggregates ( Wu et al, 2015 ). This notion is supported by the reduction in alpha-synuclein oligomers, soluble p62 protein levels, and perinuclear p62 aggregates following BAG5 KD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, another study also demonstrated that BAG3 may promote mitophagy by recruiting Parkin to the depolarized mitochondria [ 135 ]. Conversely, BAG4 and BAG5 have been implicated in disturbing the translocation of PARKIN to the mitochondria, thus suppressing mitophagy [ 139 , 140 ]. Of note, BAG5 directly binds to Parkin to suppress its E3 ligase activity for mitophagy, but promotes Parkin-mediated proteolysis degradation for PCD upon depolarization of mitochondria, indicating a role of BAG5 in switching the pro-survival and pro-death activity of Parkin [ 139 ].…”
Section: Interplay Between Mitophagy and Pcd: A New Role Of The Bamentioning
confidence: 99%